Effect of cooling channel position on heat transfer characteristics and thermoelectric performance of air-cooled PV/T system - Wu, Shuang-Ying; Wang, Ting; Xiao, Lan; Shen, Zu-Guo (Solar energy, 2019)
•Three dimensional numerical models of air-cooled PV/T systems were established.•Effect of cooling channel position on heat transfer and thermoelectric performance.•Effects of internal and external parameters under two design positions.•Comparisons were made to determine the merits of two cooling channel positions. An investigation on the effect of cooling channel position on heat transfer characteristics and thermoelectric performance of air-cooled PV/T systems has been conducted numerically. Two design positions, cooling channels above PV panel (case1) and below PV panel (case2), were considered. It is found that the effect of internal radiation in the cooling channel on the system performance is greater for case1 in comparison to case2, while an opposite behavior is presented for the cooling effect on PV panels. Except for the effect of air inlet temperature, the magnitude and variation trend of the convective Nusselt number on PV panels are almost the same for two case systems. A maximum total exergy efficiency is obtained at the air inlet temperature of 298.15 K for case1 system and 295.65 K for case2 system. From the perspective of the amount of supplied energy, the case1 system is preferred. Detailed analysis focusing on the quality of energy should be carried out to determine the merits of case1 and case2 systems.